TRACING THE ORIGIN AND EVOLUTION OF APA STYLE: FROM SIMPLE GUIDELINES TO GLOBAL STANDARD - Sameena Tabassum (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
APA Style is a documentation style adopted in academic and official writings by a large number of educational institutions and official organisations across the world. Most scientific journals and publications endorse APA Style. This paper attempts to trace the origin and the evolution of APA Style. Since its origin as an article of a few pages in 1929, APA Style has evolved from simple writing guidelines into a long document published in the form of a book of several hundred pages. Its latest edition is its seventh edition, which lays down comprehensive rules for all forms of academic text. The objective of this paper is to document the developments that have been taking place in its mechanics and specifications, across its various editions, catering to the wide variety of publications, setting the global standards for writing and publishing.